Early management of crush injury and crush syndrome: a Faculty of Pre-Hospital Care consensus statement - Felix Wood; Philip Cowburn; Jason Smith; Lauren Weekes; Timothy Godfrey; Sam Wilkins; Elizabeth Freeman; Leo Wood; Jake Gluyas-Harris; Peter Gimson; Oliver Brown; Benjamin Earle-Wright; et al. (Emergency Medicine Journal, 2026)
Guidance is required for UK prehospital care providers managing patients with suspected crush injury to minimise preventable morbidity and mortality. This consensus statement gives relevant and practicable recommendations following a structured evidence review and a consensus process. Differences between this and previous guidance reflect, in part, the context for which these recommendations are intended. The role of aggressive fluid administration and concerns regarding hyperkalaemia are de-emphasised. This consensus statement may also be relevant for providers working in other developed healthcare systems.